Synthesis, Optical Properties, and Sensing Applications of LaF(3):Yb(3+)/Er(3+)/Ho(3+)/Tm(3+) Upconversion Nanoparticles - Chien, Hsiu-Wen (Nanomaterials (Basel), 2020)
Herein, we successfully synthesized a series of LaF(3):Yb(3+)/Er(3+)/Ho(3+)/Tm(3+) upconversion nanoparticles (UCNPs) and LaF(3):Yb(3+)(0.20), Er(3+)(0.02)@LaF(3):Yb(3+)(0.20) core/shell UCNPs by modifying the amount of NaOH and the reaction time. Hexagonal LaF(3) nanocrystals with uniform particle sizes and bright UC emissions were obtained. The crystal structures of the lanthanide-doped LaF(3) UCNPs were investigated using wide-angle X-ray diffraction. The morphologies and particle sizes of the nanocrystals were determined using transmission electron microscopy. The photoluminescence (PL) spectra of the LaF(3) nanocrystals could be tuned by altering the doping ratio of Er(3+), Ho(3+), and Tm(3+). In addition, the PL intensities increased after coating the UCNP cores with an active shell. The fluorescence intensities of the UCNPs synthesized via a one-hour reaction with the addition of 2.5 or 5 mmol NaOH increased by up to 17 times compared with the sample prepared without the addition of NaOH. By modifying the doping ratio of Yb/Tm, UV-emissive LaF(3) nanocrystals were obtained. After surface modification by ligand exchange, the hydrophobic LaF(3):Yb(3+)(0.20), Er(3+)(0.02)@LaF(3):Yb(3+)(0.20) core/shell UCNPs became water-dispersible. These colloid UCNPs could be utilized as a fluorescent probe for the detection of Hg(2+) ions under 980 nm near-infrared irradiation.